Muscarinic acetylcholine receptor modulation in neurological diseases - Tobin, Andrew B. (Henry Stewart Talks, 2026)
Muscarinic acetylcholine receptors, Neurological drug discovery, Schizophrenia and Alzheimer’s disease, Structure-based drug design, Allosteric GPCR modulation